2015
DOI: 10.17772/gp/58705
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and delivery in women after genital-sparing surgical treatment of cervical cancer.

Abstract: Słowa kluczowe: rak szyjki macicy / FLąĪD / konizacja / trachelektomia /

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Basta et al observed a 76.5% pregnancy rate in patients after conization, and 90% lasted until term. Fifty per cent of patients after vaginal radical trachelectomy with laparoscopic lymphadenectomy became pregnant, but only 50% finished at term, 33% delivered preterm, and 16.7% experienced miscarriages [33].…”
Section: Introductionmentioning
confidence: 99%
“…Basta et al observed a 76.5% pregnancy rate in patients after conization, and 90% lasted until term. Fifty per cent of patients after vaginal radical trachelectomy with laparoscopic lymphadenectomy became pregnant, but only 50% finished at term, 33% delivered preterm, and 16.7% experienced miscarriages [33].…”
Section: Introductionmentioning
confidence: 99%